ANALYSIS OF RIVER BANK EROSION BY COMBINED AIRBORNE AND LONG-RANGE TERRESTRIAL LASER SCANNING: PRELIMINARY RESULTS ON THE VISTULA RIVER - S. Tyszkowski; H. Kaczmarek; S. Linowski; S. Linowski; E. A. Kozyreva (Геодинамика и тектонофизика, 2018)
In our study, high-resolution digital elevation models (HRDEM) were generated by combining the data from airborne laser scanning (ALS, 2012) and long-range terrestrial laser scanning (TLS, 2015) and used for qualitative and quantitative analysis of recent morphodynamic processes in the Vistula river bed near Nieszawa, Central Poland. The study area was a river stretch nearly 1 km long, in its lowland part, with the 440 m wide channel and 3.5‑5.0 m high banks. It is located 27 km downstream from the reservoir in Włocławek, so it is under the influence of the reservoir. The TLS measurements were performed from the opposite bank of the river, from a distance of up to 750 m. By combining the ALS and TLS data, we investigated and evaluated both the horizontal variations in the height of the river bank and changes in its profile, with a high resolution of about 900 points/m2. Our results show that in this river stretch, both the transverse profile of the river bank and the location of its upper edge have been changed during the three years between the ALS and TLS measurement sessions. The scale of this phenomenon varies from a complete lack of erosion to lowering of the upper edge of the cliff by about 1 m, in some points even up to 2 m. The applied methods allowed us to estimate the area of the observed transformations, in contrast to the conventional methods that enable only analyses in selected transverse sections.